Current Trends in Wheat Research - Ansari, Mahmood-ur-Rahman (IntechOpen, 2022)
Current Trends in Wheat Research is an interdisciplinary book dealing with diverse topics related to recent developments in wheat research. It discusses the latest research activities in biotic and abiotic stress tolerance in wheat. The book contains chapters containing valuable information on wheat diseases, insect pests, drought stress as well as water use efficiency in wheat crops.